2011
DOI: 10.1212/wnl.0b013e318217e76a
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow by arterial spin labeling in poststroke dementia

Abstract: Objective: To investigate the relationship between cerebral blood flow and dementia in older stroke survivors and subjects with Alzheimer disease (AD). Methods:This cohort study used arterial spin labeling MRI at 3 T to examine cerebral blood flow (CBF).We scanned 39 patients 6 years after stroke. They were older than 75 years at the time of stroke and free of dementia 3 months poststroke, with 8 subsequently developing dementia. We also scanned 17 subjects with AD and 29 healthy control subjects. We determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…The GM-CBF values observed here are consistent with those in other studies involving younger adults, 27 healthy older adults, 28 and individuals with chronic stroke. 29 Older adults with WMH, however, exhibited lower GM-CBF than previously reported. 30 Calibration of the GM-CBF to individual labeling efficiency on the basis of PC altered the sensitivity to distinguish clinical groups.…”
Section: Discussionmentioning
confidence: 56%
“…The GM-CBF values observed here are consistent with those in other studies involving younger adults, 27 healthy older adults, 28 and individuals with chronic stroke. 29 Older adults with WMH, however, exhibited lower GM-CBF than previously reported. 30 Calibration of the GM-CBF to individual labeling efficiency on the basis of PC altered the sensitivity to distinguish clinical groups.…”
Section: Discussionmentioning
confidence: 56%
“…27 In our more recent study on poststroke stable and dementia cases there was also no major impact on laterality of medial temporal atrophy or hippocampal microscopic changes. 28 In agreement with the harmonization standards, 6 we recommend that alternate sampling should be now widely used in prospective cohorts. We recognize, however, that even the limited number of brain regions we studied may exceed available resources on a clinical neuropathologic service.…”
Section: Discussionmentioning
confidence: 79%
“…[12][13][14] It has also been suggested that hypotension resulting from BP-lowering drugs may be more harmful than hypertension in older people with hypoperfusion producing syncope, falls, and possibly accelerating atrophy and leukoaraiosis. 15 Cognitive decline is associated with reduced CBF in the elderly, 16 and we have shown reductions in CBF are associated with poststroke dementia 17 and late life depression. 18 Preventing reductions in CBF associated with hypertension in older people might reduce the risk of cognitive impairment and mood disorders.…”
mentioning
confidence: 71%